A New GPS-based Digital Protection System for Smart Grids in Loop Structure - Liu, X.; Steurer, M.; Yu, M. (EAI Endorsed Transactions on Energy Web, 2014)
This paper presents a new digital protection system to solve the protection challenges in future smart grids, i.e., fast protection and fault isolation in a loop-structured system with limited magnitude of fault current. The new system combines two protection algorithms, i.e., a differential protection as the primary algorithm and an overcurrent protection as the backup one. The new system uses real-time Ethernet and digital data acquisition techniques to overcome the restriction on data transmission over large grids. The current measurements at different locations are time-synchronized by GPS clocks, and then transmitted to a central computer via the Ethernet. As opposed to digital relays which often contain PMU functionality nowadays, this approach uses time stamps on the instantaneous current values. We build a prototype of the new system on a test-bed. The results from simulations and experiments have demonstrated that the protection system achieves fast and accurate protection.